Answer:
![(d^(2)x )/(d^(2)t )+(k)/(m)x+(b)/(m) (dx)/(dt)=0](https://img.qammunity.org/2020/formulas/physics/college/rkbe2xwdkg2sxacwgbjdtldm8kn9xk9et6.png)
Step-by-step explanation:
The spring mass equation for the damped oscillation will be,
![F=-kx-bv](https://img.qammunity.org/2020/formulas/physics/college/j2q03n5gu2fct2tbv405dren3gabjyas9i.png)
Here, -bv is the damping term used in this b is damping constant, k is spring constant, x is elongation in the spring, F is the force.
![ma=-kx-bv\\m(d^(2)x )/(d^(2)t )=-kx-b(dx)/(dt)\\ m(d^(2)x )/(d^(2)t )+kx+b(dx)/(dt)=0\\(d^(2)x )/(d^(2)t )+(k)/(m)x+(b)/(m) (dx)/(dt)=0](https://img.qammunity.org/2020/formulas/physics/college/kq0gsz3y0nvvhclbw5b17srrg3glgs38z4.png)
Therefore the differential equation for the damped harmonic oscillator is,
![(d^(2)x )/(d^(2)t )+(k)/(m)x+(b)/(m) (dx)/(dt)=0](https://img.qammunity.org/2020/formulas/physics/college/rkbe2xwdkg2sxacwgbjdtldm8kn9xk9et6.png)